Burden and risk factors of chronic respiratory diseases in Nepal, 1990–2019: An analysis of the global burden of diseases study. Issue 2 (31st January 2023) - Adhikari, Tara Ballav; Paudel, Kiran; Paudel, Rajan; Bhusal, Sandesh; Rijal, Anupa; Högman, Marieann; Neupane, Dinesh; Sigsgaard, Torben; Kallestrup, Per
Abstract: Background and Aims: Chronic respiratory diseases (CRDs) substantially contribute to morbidity and mortality globally and in Nepal. However, there is a paucity of evidence on the trend and the burden of CRDs in Nepal. This study reports the trend of the burden and contribution of major risk factors to CRDs in Nepal from 1990 to 2019. Methods: This study is an observational study using publicly available data from Global Burden of Disease 2019 estimations for Nepal. The age‐standardized and age‐specific prevalence, incidence, mortality, disability‐adjusted life years (DALYs), and risk factors for CRDs in Nepal were extracted to measure the burden and its trend. The data are presented as percentages or as rates per 100, 000 population. Results: The age‐standardized incidence rate of CRDs in Nepal in 2019 was 913.6 per 100, 000 (95% uncertainty interval [UI]: 828.7–1000.1), which was an increase of 7.7% from 848.6 per 100, 000 (95% UI: 780.2–918.2) in 1990. However, the age‐standardized prevalence rate [4453/100, 000 (4234.2–4671.8) in 1990; 4457.1/100, 000 (4255.2–4666.8) in 2019] was almost stagnant. Most CRDs attributed to deaths and DALYs were due to chronic obstructive pulmonary disease. Conclusions: Air pollution and smoking are the main risk factors for DALYs due to CRDs in Nepal. This surging burden of the incidence rate of CRDs in Nepal calls for more effective actions to curb the risk factors and diseases.